The factors that influence turnover intention among employees in GMP Medicare Sdn. Bhd. (Top Glove) at Klang, Selangor / Nurrul Hazieqah Rohmanan - Rohmanan, Nurrul Hazieqah (Faculty of Business and Management, 2018)
This paper examines on employee turnover intention and the relationship with job stress, work engagement, job satisfaction and organizational commitment. The study highlighted and defines the basic concept of job stress, work engagement, job satisfaction and organizational commitment and turnover intention. The total population for this study consist 307 employees. The total sample size of this survey was collected by distributed 175 questionnaires and 170 return questionnaires. The data collected was processed using Statistical Package for Social Science version 20. The data had been analyzed using Descriptive, Pearson correlation and multiple regressions. Hence, the results from this study reveal that there is a positive relationship between all independent variables which job stress, work engagement, job satisfaction and organizational commitment relationship have positive relationship toward turnover intention. However, the result indicates there are many other factors that can contribute to turnover intention which are not included in this research. The sample study is only limited to the employees that are working GMP Medicare Sdn. Bhd.